2007
DOI: 10.1007/s10531-007-9230-2
|View full text |Cite
|
Sign up to set email alerts
|

Land rehabilitation and the conservation of birds in a degraded Afromontane landscape in northern Ethiopia

Abstract: The few remaining Afromontane forest fragments in northern Ethiopia and the surrounding degraded, semiarid matrix form a habitat mosaic of varying suitability for forest birds. To evaluate the effect of recent land rehabilitation efforts on bird community composition and diversity, we studied bird species distributions in ten small forest fragments (0.40-20.95 ha), five grazing exclosures (10-year-old forest restoration areas without wood extraction and grazing livestock) and three grazed matrix sites during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…If mating events occur mainly within fragments, between neighboring and possibly related trees, this may increase the risk of inbreeding and induce lower fitness in future generations (Vranckx et al 2014). Although birds, including large and small frugivores such as hornbills and thrushes, are relatively well conserved in the church forests (Aerts et al 2008), and although the regionwide establishment of grazing exclosures during the previous decades may have provided stepping stones and an improved landscape connectivity for seed vectors (Aerts et al 2008), it is unclear to what extent these birds act as effective seed dispersal vectors. Also, if mating patterns are mainly local and offspring therefore potentially inbred, seed dispersal may have a limited genetic rescue effect and therefore it remains unclear if birds reduce functional forest isolation at all.…”
Section: Field Survey Data Reveal High Floristic Variabilitymentioning
confidence: 99%
“…If mating events occur mainly within fragments, between neighboring and possibly related trees, this may increase the risk of inbreeding and induce lower fitness in future generations (Vranckx et al 2014). Although birds, including large and small frugivores such as hornbills and thrushes, are relatively well conserved in the church forests (Aerts et al 2008), and although the regionwide establishment of grazing exclosures during the previous decades may have provided stepping stones and an improved landscape connectivity for seed vectors (Aerts et al 2008), it is unclear to what extent these birds act as effective seed dispersal vectors. Also, if mating patterns are mainly local and offspring therefore potentially inbred, seed dispersal may have a limited genetic rescue effect and therefore it remains unclear if birds reduce functional forest isolation at all.…”
Section: Field Survey Data Reveal High Floristic Variabilitymentioning
confidence: 99%
“…A study in the extremely fragmented and dry northern part of Ethiopia showed the occurrence of more species and a higher number of unique species in the forest patches than in open fields (Aerts et al, 2008). Therefore, understanding the effect of habitat disturbance on bird community structure is important to prioritize future conservation of biodiversity that are under great pressure either due to natural or human induced disturbances (Girma Mengesha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the Ethiopian landscape is altered by agricultural activities, deforestation and overgrazing (Aerts et al, 2008). Habitat deterioration is particularly threatening quality of the ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the landscape mosaics of southwest Ethiopia may approximate the best of conservation strategies, in which remnant natural vegetation remains relatively intact while a high-quality humanmodified matrix is also maintained (Lindenmayer & Franklin 2002;Donald & Evans 2006;Fischer et al 2006). Ecological studies aimed at guiding conservation policy or biodiversity-focused certification schemes in complex landscape mosaics may be most effective if both forest patches and the agricultural matrix are considered simultaneously to grasp comprehensively the threats to biodiversity and consider most appropriate levels of management (Aerts et al 2008;Harvey et al 2008). Here we analyze the dilemma that coffee cultivation may present for habitat conservation in the Ethiopian landscape; coffee cultivation may introduce or maintain trees in open farmland, while at the same time modify forest remnants.…”
Section: Introductionmentioning
confidence: 99%